2011
DOI: 10.1007/s00256-011-1306-0
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided injection for MR arthrography of the hip: comparison of two different techniques

Abstract: The femoral neck injection technique provides high intraarticular contrast volume and produces less extraarticular contrast leakage than the femoral head injection technique when US guidance is used for MR arthrography of the hip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Kantarci et al 13 randomised patients into two arms (comparing two different US-guided approaches) and adequately blinded participants, study personnel and outcome assessors, and also concealed allocation. (4) One of the eight single-arm studies had an independent investigator who did not perform the injection accuracy assessment 18.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Kantarci et al 13 randomised patients into two arms (comparing two different US-guided approaches) and adequately blinded participants, study personnel and outcome assessors, and also concealed allocation. (4) One of the eight single-arm studies had an independent investigator who did not perform the injection accuracy assessment 18.…”
Section: Resultsmentioning
confidence: 99%
“…(4) One of the eight single-arm studies had an independent investigator who did not perform the injection accuracy assessment 18. (5) One study had four participant drop-outs (1, needle phobia; 3, MRI claustrophobia); these four patients were eliminated from the analysis 13. (6) All studies reported the accuracy of the injections, and none had selective reporting.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations